2017
DOI: 10.5194/asr-14-23-2017
|View full text |Cite
|
Sign up to set email alerts
|

NAO and extreme ocean states in the Northeast Atlantic Ocean

Abstract: Abstract. Large scale atmospheric oscillations are known to have an influence on waves in the North Atlantic. In quantifying how the wave and wind climate of this region may change towards the end of the century due to climate change, it is useful to investigate the influence of large scale oscillations using indices such as the North Atlantic Oscillation (NAO: fluctuations in the difference between the Icelandic low pressure system and the Azore high pressure system). In this study a statistical analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Further work is required to increase confidence in these results since uncertainty remains in the future position of the jet stream, in particular in the North Atlantic (IPCC, 2013;Gallagher et al, 2016), and subsequently the projected changes in wave heights. Additionally, recent research suggests that the effect of the North Atlantic Oscillation (NAO) should be taken into account when considering future extremes in the North Atlantic, as a positive phase may in fact enhance extremes of significant wave height (Gleeson et al, 2017).…”
Section: Climate Changementioning
confidence: 99%
“…Further work is required to increase confidence in these results since uncertainty remains in the future position of the jet stream, in particular in the North Atlantic (IPCC, 2013;Gallagher et al, 2016), and subsequently the projected changes in wave heights. Additionally, recent research suggests that the effect of the North Atlantic Oscillation (NAO) should be taken into account when considering future extremes in the North Atlantic, as a positive phase may in fact enhance extremes of significant wave height (Gleeson et al, 2017).…”
Section: Climate Changementioning
confidence: 99%
“…In an additional study, focusing on extreme wave events off Ireland, Gleeson et al (2017) found evidence of some extreme wave enhancement under the influence of a strongly positive North Atlantic Oscillation, off the west coast of Ireland. Further studies are required to try to address the current uncertainties in North Atlantic wave and storm projections and their affect on Ireland.…”
Section: Introductionmentioning
confidence: 96%
“…However, a clear dependency between the storm's frequency and the low-frequency atmospheric variability such as the North Atlantic Oscillation (NAO) has been previously found (Gleeson et al, 2017;Rogers, 1997;Semedo et al, 2011;Wang & Swail, 2001). However, a clear dependency between the storm's frequency and the low-frequency atmospheric variability such as the North Atlantic Oscillation (NAO) has been previously found (Gleeson et al, 2017;Rogers, 1997;Semedo et al, 2011;Wang & Swail, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Storm dynamics in the North Atlantic has a typical time scale of days. However, a clear dependency between the storm's frequency and the low-frequency atmospheric variability such as the North Atlantic Oscillation (NAO) has been previously found (Gleeson et al, 2017;Rogers, 1997;Semedo et al, 2011;Wang & Swail, 2001). Depending on the NAO phase, different weather regimes (e.g., wind regimes; Cassou et al, 2011), mean, and extreme wind and wave conditions develop over the North Atlantic.…”
Section: Introductionmentioning
confidence: 99%